Carbon nanotubes induced fibrogenesis on nanostructured substrates. Issue 3 (10th February 2017) - Wang, Kai; He, Xiaoqing; Linthicum, Will; Mezan, Ryan; Wang, Liying; Rojanasakul, Yon; Wen, Qi; Yang, Yong
Abstract : The fibrogenic response of lung fibroblasts to carbon nanotubes is regulated by the substrate nanotopography through modulating cell spreading and elongation. Abstract : While the rapidly evolving nanotechnology has shown promise in electronics, energy, healthcare and many other fields, there is increasing concern about the adverse health consequences of engineered nanomaterials. To accurately evaluate the toxicity of nanomaterials, in vitro models incorporated with in vivo microenvironment characteristics are desirable. This study aims to delineate the influence of nanotopography on the fibrogenic response of normal human lung fibroblasts to multi-walled carbon nanotubes (MWCNTs). Nanoscale gratings and pillars of various heights were fabricated on polydimethylsiloxane substrates. Cell spreading and biomechanics were measured, and fibrogenic responses including proliferation, collagen production and reactive oxygen species generation of the fibroblasts grown on the nanostructured substrates in response to MWCNTs were assessed. It was observed that the cells could be largely stretched on shallow nanogratings, leading to a stiffer cytoskeleton and nucleus, enhanced cell proliferation and collagen production, and consequently, the toxic response sensitivity of the fibroblasts was undermined. In contrast, the cell spreading and stiffness could be reduced using tall, isotropic nanopillars, which significantly improved the cell toxic sensitivity to the MWCNTs. In addition to highlighting the significant influence of cell–nanotopography interactions on cell sensing CNTs, this study contributed to the development of physiologically relevant in vitro models for nanotoxicology studies.